Perbandingan Efektivitas Totok Wajah dengan Terapi Musik Klasik terhadap Tingkat Cemas dan Nyeri pada Remaja Dismenore Primer - Fitrya Anggraini; Saidah Syamsuddin; Andi Nilawati Usman; Wardihan Sinrang; Muhamad Tamar; Suryani As'ad (Poltekkes Kemenkes Palu, 2022)
Introduction: In each country more than 50% of the average woman still experiences menstrual pain. Meanwhile, in Indonesia, it is estimated that 55% of women of reproductive age suffer from pain during menstruation. The purpose of the study was to review non-pharmacological interventions regarding facial acupressure (BL-2, Yin Tang, GV 23, GB 15, Tai Yang, GB 14, Ex Hn4, TE 23, Sang Ming, LI-20, Ex Hn 8, ST-3, Si 18, Du 26, REN 24, JiaCenjiang, SJ21, SJ17, GB-2) and Mozart classical music in reducing pain in primary dysmenorrhea. Methods: This research is quantitative with a quasi-experimental design. The approach in the research used is pre-post test design. In November-January 2022 at Megarezky University Makassar. The sample in this study were 28 dysmenorrheal adolescents aged <25 years who were divided into two groups, namely a full-blooded face and classical music group. Results: There were pre and post differences in the acupressure and classical music groups with pain intensity (p=0.002). And there was no significant difference between the full-blooded face group and classical music (p=0.20<0.05). Conclusion: There is an effect of giving face acupressure and classical music in reducing pain and anxiety in primary dysmenorrhea.